(untitled) (Web of Teachers: Inderscience Research, 2024)
The purpose of organizing definite and indefinite articles in English classes is to help you speak and write clearly and without mistakes in English. The main purpose of writing this essay is to learn the rules of the place and use of articles in English and in what situations they are used.